Application of ontology modularization to human-web interface design for knowledge sharing - Wang, Hai; Wang, Shouhong (Expert systems with applications, 2016)
•An ontology is an explicit semantic network instead of a hierarchy of concepts.•Ontology can be a tool for human-web interface design for knowledge sharing.•Modularization is a key subject of ontology for human-web interface design.•The usefulness of ontology modularization for human-web interface design is demonstrated. Ontology has received considerable attention in the semantic technology community. This paper discusses the roles of ontology modularization in human-web interface design for knowledge sharing. It stresses that ontology can support human-web interaction as a key component of knowledge sharing on the Internet. The paper proposes an approach of ontology modularization to navigating and searching web portals for the purposes of knowledge sharing. A case study of human-web interface design using ontology modularization for a commercial software web portal is used to illustrate the application of the proposed approach.